Podter Program Analysis (Latest Podcast) Bengkuluekspress.Com - Santia, Suci Anugrah; Putra , Dilmai; Maryaningsih, Maryaningsih (Utami Publisher, 2025)
The media plays an important role in shaping public opinion through the selection of issues presented and the way they are presented. This research examines how the media, especially the podter program in Bengkulu Ekspress, sets the agenda through various platforms and interactions with the public. Based on interviews with key informants and principal informants, the findings show that the media not only reflects reality, but also shapes it by selecting issues that are relevant and interesting to the public. Issues that are often raised include politics, business, tourism and local achievements, with a focus on things that are viral or have urgency for society. Podter programs broadcast live via platforms such as Facebook and YouTube allow direct interaction between the source and the audience, creating space for public opinion to influence the themes raised. Setting this agenda also involves two levels: first, determining the issue to be highlighted, and second, the specific attributes of the issue that shape the public's assessment of the importance of the issue. The results of this research show that the media in Bengkulu Ekspress plays a role as social control by providing a platform for the public to interact, provide responses, and obtain information that is educational, informative, and promotional. The podter program is expected not only to convey information but also as a tool to influence and shape public opinion.